Many-body correlations for nuclear physics across scales: from nuclei to quark-gluon plasmas to hadron distributions - Giacalone, Giuliano (The European physical journal. A, Hadrons and nuclei, 2023)
It is an experimental fact that multi-particle correlations in the final states of high-energy nucleus-nucleus collisions are sensitive to collective correlations of nucleons in the wave functions of the colliding nuclei. Here, I show that this connection is more direct than it intuitively seems. With an energy deposition scheme inspired by high-energy quantum chromodynamics, and within a linearized description of initial-state fluctuations in the quark-gluon plasma, I exhibit relations between N-particle correlations in the final states of nuclear collisions and N-nucleon density distributions in the colliding nuclei. This result formally justifies the sensitivity of the outcome of high-energy collisions to features such as nuclear deformations. It paves the way, thus, to systematic studies of the impact of state-of-the-art nuclear interactions in such processes.
Gesehen am 25.03.2025